2008
DOI: 10.1094/cchem-85-1-0019
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Shelled Corn Fungal Susceptibility to Carbon Dioxide Evolution and Kernel Attributes

Abstract: Fifty‐one samples of shelled corn were rewetted to 21% wb moisture content (MC) and evaluated for susceptibility to fungal invasion using ergosterol measurements and a test kit that measures carbon dioxide (CO2) evolution. The sample attributes measured were percent germination, electrolyte leakage after soaking in deionized water, percent fines, and percent kernel infection. The difference in ergosterol content before and after incubation at 24°C was used as the standard measure of fungal growth. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…4) presented a linear trend for all treatments, as opposed to the equivalent conditions for kernels, in which an exponential curve was observed after a short lag phase (Friday et al, 1989;Wilcke et al, 2001;Moog et al, 2008). Following the regression model observed in this study, important losses would be reached (almost 25% over six months) if the deterioration rate for six months fits the rate observed in this study (table 3), hence the importance of extending the study for prolonged times.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…4) presented a linear trend for all treatments, as opposed to the equivalent conditions for kernels, in which an exponential curve was observed after a short lag phase (Friday et al, 1989;Wilcke et al, 2001;Moog et al, 2008). Following the regression model observed in this study, important losses would be reached (almost 25% over six months) if the deterioration rate for six months fits the rate observed in this study (table 3), hence the importance of extending the study for prolonged times.…”
Section: Resultssupporting
confidence: 68%
“…Many authors (Wilcke et al, 2001;Bern et al, 2002;Chitrakar et al, 2006;White, 2007;Moog et al, 2008) quantified corn kernel deterioration due to fungal growth with different conditions of moisture, temperature, mechanical damage, genetic hybrid resistance, ozone treatment, and fungicide treatment. Nevertheless, little is known about handling and appropriately storing cellulosic biomass for biofuel production.…”
mentioning
confidence: 99%
“…Managers of elevators, storage facilities, or processing plants have little or no information about these factors and must assess the likelihood of spoilage by visually examining a sample of shelled corn and measuring its moisture content (MC). As stated previously (Moog et al 2008), we believe that a relatively simple carbon dioxide (CO 2 ) test kit can be used to assess susceptibility of shelled corn to fungal invasion. Fungal susceptibility, as it is used here, is defined as the likelihood that fungi will grow during subsequent storage or shipment if the shelled corn is subjected to conditions conducive to fungal growth.…”
mentioning
confidence: 93%
“…In an earlier study (Moog et al 2008), we used a test kit to measure CO 2 evolution from samples rewetted to 21% MC and incubated at 24°C for ≤80 hr. We assumed that fungal growth during the incubation period could be assessed on the basis of difference in ergosterol before and after testing and concluded that CO 2 evolution measured using the test kit was a reasonable measure of fungal susceptibility.…”
mentioning
confidence: 99%
See 1 more Smart Citation